2021
DOI: 10.1177/02676591211042733
|View full text |Cite
|
Sign up to set email alerts
|

The association of left ventricular histologically verified myocardial fibrosis with pulmonary hypertension in severe aortic stenosis

Abstract: Objectives: To evaluate the association between histologically verified left ventricular (LV) myocardial fibrosis (MF) and its bio- and functional markers with pulmonary hypertension (PH) in severe aortic stenosis (AS). Methods: About 34 patients with isolated severe AS underwent 2D echocardiography, cardiac magnetic resonance (CMR) imaging, and plasma NT-proBNP evaluation before aortic valve replacement (AVR). LV measurements were analyzed by CMR and LV strain using feature tracking software (Medis Suite QStr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In particular, LV fibrosis area and LV global longitudinal strain were valuable predictors for detecting the presence of PH in severe AS. In another study in 2021, the same working group led by Gumauskiene et al [58] showed in a very similar patient population with concurrent endomyocardial biopsy that histologically detectable diffuse myocardial fibrosis correlated positively with LV dilatation and negatively with LV dysfunction, global longitudinal strain and circumferential strain, respectively.…”
Section: Mrimentioning
confidence: 88%
“…In particular, LV fibrosis area and LV global longitudinal strain were valuable predictors for detecting the presence of PH in severe AS. In another study in 2021, the same working group led by Gumauskiene et al [58] showed in a very similar patient population with concurrent endomyocardial biopsy that histologically detectable diffuse myocardial fibrosis correlated positively with LV dilatation and negatively with LV dysfunction, global longitudinal strain and circumferential strain, respectively.…”
Section: Mrimentioning
confidence: 88%
“…In patients with AOS, patchy LGE accumulates over time and is associated with more severe valve stenosis and LV dysfunction [ 97 ]. The extent of LV myocardial fibrosis measured by MRI and validated by endomyocardial biopsy in AOS patients correlated with PH severity [ 98 ].…”
Section: Casementioning
confidence: 99%